(untitled) (Revista de Ciências Agroveterinárias, 2023)
Globalization, population change, and rural-to-urban movement are the main causes of the enormous issues faced by rural communities. Every growing nation, including the Kurdistan Region of Iraq (KRI), has a sizable proportion of rural farmers among its populace. This study was done in the Sulaimani Governorate, which was divided into six main districts namely; Garmian, Penjwin, Halabja, Chamchamal, Sharazur, and Raniya, and aimed to compare the groundwater level with summer crop water demand. The weighted Sum Method (WSM) and a Normalized Difference Vegetation Index map (NDVI) were used to analyze and illustrate the current water demand status for summer crops. The study employed a participatory research design, utilizing a purposive sampling method to select 60 representative farmers, 25 key decision-makers, representatives from Non-Governmental Organizations (NGOs), and experts in the field of water management. Data was collected through the use of focus group discussions (FGDs) and Key Informant Interviews (KIIs) to gather information from the selected participants. This study is innovative in its attempt to establish a correlation between the yield of summer crops and the availability of groundwater. As a conclusion for this study, the results suggest that the level of groundwater plays a significant role in determining the production of summer crops. Additionally, the sustainable development of various regions within the Sulaimani Governorate is influenced by a complex interplay of environmental, economic, and social factors. Future work will be focus on doing a detail research regarding time series for ground water level (GWL) vs. crop production vs. NDVI.